Warm Bodies - Marion, Isaac, 1981- (Atria Books, 2012)
A zombie who yearns for a better life ends up falling in love with a human, in this original debut novel. R is a zombie. He has no memories, no identity, and no pulse, but he has dreams. He doesn't enjoy killing people; he enjoys riding escalators and listening to Frank Sinatra. He is a little different from his fellow Dead. Not just another zombie novel, this is funny, scary, and deeply moving.